The Influence of Product Variation, Service Quality, Product Quality, Price, and Location on the Purchasing Decisions of UMKM Darti Snack Products in Winduaji Village - Dyah Nanda Imtiaz; Sugeng Rianto (International Research & Development for Human Beings (IRDH), 2026)
This study aims to analyze the effect of product variety, service quality, product quality, price, and location on purchasing decisions at UMKM Darti Snack in Winduaji Village, Paguyangan District, Brebes Regency. The sample consisted of 250 respondents selected using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that service quality, product quality, price, and location have a positive effect on purchasing decisions, while product variety does not have a positive effect. The R-square value of 0.674 shows that the model explains 67.4% of the variance in purchasing decisions. This study suggests that UMKM Darti Snack should improve service quality, product quality, pricing strategies, and maintain location accessibility to enhance purchasing decisions. Although product variety has no direct effect, it should still be considered to support business competitiveness.